ANTI DUMPING DALAM GENERAL AGREEMENT ON TARIFFS AND TRADE (GATT) DAN PENGARUHNYA TERHADAP PERATURAN ANTI DUMPING INDONESIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The most widely used remedy for unfair trade is the antidumping duty. "Dumping." in the trade context, refers to the practice of discriminatory pricing by individual sellers, who offer product at a lower price in a foreign market than they do in their domestic markets. A WTO member .finding that dumping by another member has caused material injury to one of its own domestic industries may impose an antidumping duty calculated to raise the price of the dumped goods to its domestic level in the exporting country. Antidumping laws provide relief to domestic industries that have suffered material injury or threatened with material injury as a result of competing imports being sold at prices shown to be less than their fair market value (LTFV). Antidumping laws and actions are often controversial because many trade experts view them as protectionist Article VI of GATT 1994 authorizes WTO members to impose antidumping duties in addition to other Tariffs if domestics officials find that imports of a specific product are sold at less than normal value and the imports cause or threaten injury to a domestic injury, or materially retard its establishment Kata kunci: anti dumping, perdagangan internacional, GATE peraturan